Liars or Self‐Deceived? Reflections on Political Deception. (15th July 2015) - Galeotti, Anna Elisabetta
Abstract : This paper contributes to the issue of political deception by exploring the role of self‐deception in democratic politics. Within politics, deception of the people is actually very often produced by the self‐deception of political leaders and officials, which is then supplemented by mechanisms of self‐deception of the public itself. That self‐deception, rather than simply straightforward deception, is a significant obstacle to truth and transparency in democratic politics is often hinted at by political scientists and historians but never properly pursued. And yet it should be, for which one of them is the case has important normative implications. This paper briefly presents the notion of self‐deception and offers some reasons to take its presence in politics seriously. It also counters possible objections to doing so. Different kinds of political self‐deception are presented and illustrated through historical examples so as to provide a clear typology and make the case for self‐deception in politics stronger.